On the performance of coded copper wire systems for G-fast communications - Ali Jaber Al-Askery; Ali Mhidi Hammadi (Institute of Advanced Engineering and Science, 2019)
This paper aims to investigate the performance of different channel coding techniques over copper wire channels. First, Chen model is used to simulate the copper wire channel model, then the performance of LDPC coded system with DVB-S2 standard is compared to the performance of turbo coded, and convolutional coded systems over wired channels. In addition, the performance of the systems under consideration is further investigated in the presence of impulsive noise (IN) with IN cancellation technique. Matlab simulations are utilized to simulate these systems for different quadrature amplitude modulations (QAM). The results have shown that LDPC coded system with large block length have outperforms the performance of the considered coding techniques.